La Divine Comédie de Dante Alighieri : une relecture biographique à des fins eschatologiques - Catherine Guimbard (Perspectives Médiévales)
This article recounts Dante’s biographical and poetical itinerary considered as oriented towards a renovatio spirituale. It analyses the role played by love, philosophy and theology in this renovation.